1989
DOI: 10.1002/1097-0142(19890601)63:11<2234::aid-cncr2820631130>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Epidural metastases in prospectively evaluated veterans with cancer and back pain

Abstract: Ninety-five male veterans with cancer and back pain were prospectively evaluated for epidural metastases. The evaluation included vertebral roentgenograms and a myelogram. The most common cancers were lung and prostate. Forty-three percent of the patients had an epidural metastasis, including 73% of the 37 patients with myelopathy and 48% of the 29 patients with radiculopathy. None of the 29 patients who had back pain without radiculopathy or myelopathy had an epidural metastasis. Thirty-seven patients were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Several prior studies of SEM suggested that patients who walk after SEM treatment live longer [9,13,[19][20]. Some of the difference in survival for ambulatory versus nonambulatory patients may have resulted from differences in the aggressiveness of individual cancers [1][2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prior studies of SEM suggested that patients who walk after SEM treatment live longer [9,13,[19][20]. Some of the difference in survival for ambulatory versus nonambulatory patients may have resulted from differences in the aggressiveness of individual cancers [1][2].…”
Section: Discussionmentioning
confidence: 99%
“…The RT protocol and dexamethasone dose were the same for all subjects reported here. The SEM treatment protocol was similar to the protocols used in several prior studies of SEM [4,9,[12][13][14]. Patients were considered ambulatory if they could walk without human assistance at least 50 feet without stopping.…”
Section: Introductionmentioning
confidence: 99%
“…Pain control is an important issue for people with cancer, especially epidural cancer [6][7][8][9][10][11]. In studies of SEMs, pain was usually the initial manifestation of the spinal cancer and the most common symptom when the SEMs were recognized [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Although the question of whether incidentally detected SEMs should be treated has not been definitively answered, radiation oncologists typically include them in treatment ports, and their presence unquestionably affects surgical decision making. Consequently, many authorities recommend either imaging the entire spine cord [11,[29][30][31] or at least the thoracic and lumbar spine in addition to the symptomatic region; asymptomatic epidural deposits are rarely found in the cervical spine [32].…”
Section: Mrimentioning
confidence: 99%